Size‐dependent dual emission of Cu, Mn:ZnSe QDs: Controlling both emission wavelength and intensity. (31st January 2017) - Xu, Shuhong; Jiang, Han; Dong, Renjie; Lv, Changgui; Wang, Chunlei; Cui, Yiping
Abstract: Cu, Mn:ZnSe quantum dots (QDs) of tunable size, controllable photoluminescence (PL) intensity ratio and PL range were prepared. A study of the experimental conditions confirmed that the size of Cu, Mn:ZnSe QDs is affected by the pH of the solution, the speed at which the Zn solution is injected and the reaction temperature. In general, high pH, low injection speed and high reaction temperature are optimal for preparing large QDs. Based on this knowledge, different sizes of Cu, Mn:ZnSe QDs were synthesized. Moreover, white emission Cu, Mn:ZnSe QDs were designed by controlling the experimental conditions and the feeding mole ratio of Mn:Cu.